Revisionary systematics of the endemic soft coral fauna (Octocorallia: Alcyonacea: Alcyoniina) of the Agulhas Bioregion, South Africa - Mcfadden, Catherine S.; Ofwegen, Leen P. Van (Zootaxa, 2017)
The Agulhas Bioregion of southern South Africa supports a unique octocoral fauna that is entirely endemic to the region. Recent molecular phylogenetic studies indicate that this endemism extends to deeper taxonomic levels than had previously been recognized, and that most of these endemic species belong to genera and families that are also endemic to South Africa. Here we revise the taxonomy of soft corals (subordinal group Alcyoniina) that were previously assigned to the cosmopolitan families Alcyoniidae, Nephtheidae and Nidaliidae, describing three new families endemic to South Africa, along with four new genera and four new species. We reassign the endemic genera Acrophytum, Pieterfaurea and Lampophyton to Acrophytidae n. fam, and describe a new species of Lampophyton, L. spinatum n. sp. The endemic species Protodendron bruuni is reassigned to a new, monotypic genus, Corymbophyton bruuni n. comb., and family, Corymbophytidae n. fam. The endemic genus Leptophyton is placed in a third new family, Leptophytidae n. fam., along with three new genera that are established for species previously assigned to Alcyonium: Circularius wilsoni n. comb., Porphyrophyton distinctum n. comb., and Tenerodus fallax n. comb. In addition, we describe new species of Leptophyton, L. fustis n. sp.; Tenerodus, T. pollex n. gen. n. sp.; and Alcyonium, A. dolium n. sp.; reassign Protodendron verseveldti to Tenerodus verseveldti n. comb.; and reassign the endemic genus Dimorphophyton to family Paralcyoniidae. Although molecular phylogenetic analyses unite Acrophytidae, Corymbophytidae and Leptophytidae within a well-supported monophyletic group, both morphological and molecular distinctions support maintaining them as three separate families. These revisions increase the number of endemic species of shallow-water soft corals known from the Agulhas Bioregion to 40, and the number of endemic genera to 13.